Early corticospinal tract sub-pathway lesion load and integrity predict post-stroke motor outcomes - Wen, Xin; Zeng, Wentao; Li, Chiyin; Qin, Yue; Qiao, Yanqiang; Lu, Tao; Dun, Wanghuan; Zhang, Ming; Mu, Junya (Frontiers in Human Neuroscience, 2025)
IntroductionGrowing evidence suggests that corticospinal tract (CST) damage and microstructural integrity are key predictors of post-stroke motor impairment. However, their combined clinical utility—particularly in CST sub-pathways originating from non-primary motor cortical areas—remains underexplored. This study aimed to determine whether microstructural integrity and lesion load (LL) of each CST sub-pathway at 2 weeks predict motor outcomes at 2, 6, and 12 weeks post-stroke.MethodsFifty seven participants completed motor and neuroimaging evaluations at 2 weeks post-stroke and underwent follow-up motor assessments at 6 (n = 37) and 12 weeks (n = 34). The integrity of the CSTs was quantified using diffusion spectrum imaging (DSI), while CST-LL was measured using structural magnetic resonance imaging, both based on the sensorimotor area tract template atlas. Stepwise multiple linear regression models were used to assess the predictive value of CST microstructural integrity and CST-LL in each sub-pathway at 2 weeks for motor function at 2, 6, and 12 weeks post-stroke.ResultsThe results indicated CST integrity and CST-LL were both the main determinants of motor deficit at 2 weeks post-stroke. Specifically, the integrity of CSTs from the primary motor cortex (M1), reflected by fractional anisotropy, emerged as a significant predictor of post-stroke motor deficit at 2 weeks, whereas CST integrity from the dorsal premotor cortex (PMd), reflected by generalized fractional anisotropy, quantitative anisotropy, and radial diffusivity. CST-LL originating from non-M1 motor areas, such as primary sensory cortex (S1), were also the main determinants for motor impairment at 2 weeks post-stroke. However, compared to CST integrity, CST-LL from non-M1 motor areas, including both the PMd and S1, were more dominant predictors, explaining 68.3% (R2adjusted = 0.683, p < 0.001) and 79.5% (R2adjusted = 0.795, p < 0.001) of the variance in motor outcomes at 6 and 12 weeks.ConclusionThe microstructural integrity of the PMd tracts and CST-LL from the non-M1 motor areas may be promising biomarker for post-stroke motor impairment. These findings highlight the pivotal role of non-M1 tracts in post-stroke motor function, particularly the PMd tracts, as a potential intervention target to enhance motor recovery.